Uneven time-space of unpaid reproductive work: an intersectional analysis of the Balearic Islands - Martín-Gago, Paula; Vives-Miró, Sònia (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
This paper aims to examine the relationship between social reproduction and the production of space and, more specifically, the role of unpaid reproductive work in the unequal production of urban space. Although many studies have addressed the social dimension of space in cities, there nevertheless remains a lack of theory relating to the production of space through the oppression and privilege associated, with or caused by, the relations of social reproduction. With the aim of helping to fill this gap, the spatiality of unpaid reproductive work was studied through intersectional analysis. This was done by exploring the spatial practice of the temporary load of unpaid reproductive work as an element responsible for inequality and by relating this to the dimensions of: 1) space and time, and 2) class, sex and age. This intersectional approach allowed us to analyse inequalities in social reproduction and identify spaces of privilege and spaces of oppression in terms of unpaid reproductive work. The study focused on the Balearic Islands and used the latest Time Use Survey (TUS) available in Spain. It is a dialogue between critical urban geography, urban sociology and feminist theory, which makes it possible to visualise the power relations and urban inequality that have derived from the sexual division of labour within the logic of historical capitalism.